Accumulated Heavy Metals Pb, Cd And Cr in Avicennia Marina Around The Ex-Bauxite Mining Area in Tanjungpinang City - Diana Azizah; Rasoel Hamidy; Mubarak Mubarak; Efriyeldi Efriyeldi; Sri Murtin (ECOTONE, 2021)
The former mining area in Tanjungpinang City was found around the Carang River and Senggarang Village. There was sedimentation containing red mud from the rest of the mining activities that covered the mangrove substrate. The impact is expected to affect the life of the surrounding mangroves. One of the dominant species found is Avicennia marina. This study aims to determine the absorption ability of heavy metal A. marina found around the former bauxite mining area of Tanjungpinang City. The study was conducted from April to August 2020. The study was conducted by a survey by sampling the sediment around the A. marina tree and its organs (roots, stems, and leaves) in the laboratory using the Atomic Absorption Spectrophotometer (AAS). The results of the analysis showed that the concentration of Pb in the sediment ranged from 0.2215-0.2711 ppm; Cd concentration ranged from 0.0113-0.0721 ppm; and Cr ranged from 0.0221-0.0633 ppm. The highest average metal concentration value for Pb was in the Carang River (root organ with a value of 2.1691 ppm); Cd metal in Senggarang (stem, 0.0951 ppm); and Cr metal in Senggarang (root, 0.4988 ppm). The phytoaccumulation mechanism of Pb, Cr, and Cd by A. marina is rhizofiltration (TF<1), while the BCF value indicates that A. marina is non-accumulator/low accumulator (BCF < 250 ppm).